2016
DOI: 10.1016/j.fertnstert.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of circulating microRNAs as a biomarker for unexplained recurrent spontaneous abortion

Abstract: Circulating microRNAs may be involved in URSA pathogenesis and provide a promising new diagnostic biomarker for URSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…The data generated by the q-PCR assay were consistent with the microarray analyses, and the correlation-coefficient between the mean values of ten individuals generated by both techniques for each miRNA was statistically significant (Supplementary Figure S1A and Supplementary Table S1), indicating the reliability of the array data generated by miRNA microarray. In this study, many miRNAs associated with azoospermia, such as miR-199a-5p21, miR-181a22, miR-22123, miR-14119, and miR-4291924, were found to be significantly modulated by exposure to MC-LR (Table 1). Moreover, some miRNAs involved in the mechanisms of other reproductive system diseases, including the urinary tract tumor, prostate cancer, and genital tumor, were also detected25262728.…”
Section: Resultsmentioning
confidence: 60%
“…The data generated by the q-PCR assay were consistent with the microarray analyses, and the correlation-coefficient between the mean values of ten individuals generated by both techniques for each miRNA was statistically significant (Supplementary Figure S1A and Supplementary Table S1), indicating the reliability of the array data generated by miRNA microarray. In this study, many miRNAs associated with azoospermia, such as miR-199a-5p21, miR-181a22, miR-22123, miR-14119, and miR-4291924, were found to be significantly modulated by exposure to MC-LR (Table 1). Moreover, some miRNAs involved in the mechanisms of other reproductive system diseases, including the urinary tract tumor, prostate cancer, and genital tumor, were also detected25262728.…”
Section: Resultsmentioning
confidence: 60%
“…Zhang et al reported that low serum miR-320b expression could act as a novel indicator of carotid atherosclerosis (29). Moreover, Qin et al provided evidence that elevating the expression of circulating miRNA-320b might serve as a biomarker for unexplained recurrent spontaneous abortion (URSA) (30). However, limited studies were focused on the role of miRNA-320b as an important regulator in tumor with its pathological role in glioma still poorly understood.…”
Section: No Of Patients --------------------------------------------mentioning
confidence: 99%
“…Qin et al showed that miR-559 might be involved in the pathogenesis of unexplained recurrent spontaneous abortion. 22 Chen and his colleagues revealed that miR-559 and miR-548d-3p could synergistically inhibit the expression of the oncogene ERBB2. 23 Yang et al 9 reported that miR-559 function as a tumor suppressor in glioblastoma multiform, and its inhibitory effect was related to metadherin and PTEN-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%